2013
DOI: 10.1073/pnas.1303002110
|View full text |Cite
|
Sign up to set email alerts
|

Stapled α−helical peptide drug development: A potent dual inhibitor of MDM2 and MDMX for p53-dependent cancer therapy

Abstract: Stapled α−helical peptides have emerged as a promising new modality for a wide range of therapeutic targets. Here, we report a potent and selective dual inhibitor of MDM2 and MDMX, ATSP-7041, which effectively activates the p53 pathway in tumors in vitro and in vivo. Specifically, ATSP-7041 binds both MDM2 and MDMX with nanomolar affinities, shows submicromolar cellular activities in cancer cell lines in the presence of serum, and demonstrates highly specific, on-target mechanism of action. A high resolution (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
762
2
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 598 publications
(804 citation statements)
references
References 45 publications
20
762
2
7
Order By: Relevance
“…Although the detailed mechanism of p53 inhibition by MDMX is still unclear, previous studies using p53-mimetic peptides and small molecule disruptors showed that MDMX-p53 binding is a critical step for p53 inactivation (18,19). MDMX-p53 binding is stimulated by CK1α, which is a major binding partner of MDMX.…”
Section: Discussionmentioning
confidence: 99%
“…Although the detailed mechanism of p53 inhibition by MDMX is still unclear, previous studies using p53-mimetic peptides and small molecule disruptors showed that MDMX-p53 binding is a critical step for p53 inactivation (18,19). MDMX-p53 binding is stimulated by CK1α, which is a major binding partner of MDMX.…”
Section: Discussionmentioning
confidence: 99%
“…By sampling alternative staple positions, interrogating cellular uptake, and correlating biochemical function with antitumor activity and mechanism of action, we have generated lead compounds that form the basis for therapeutic development (16,17,19,20). Here, we report the application of all-hydrocarbon stapling to recapitulate the native primary sequence and secondary structure of the RAS-interacting α-helix of SOS1.…”
mentioning
confidence: 99%
“…Added to this difficulty has been the complexity of the ubiquitin system, with ligases having many substrates and many proteins being substrates for multiple ligases (6,9). Despite these problems, peptide and small molecule inhibitors have been successfully obtained that specifically target the substrate binding site of Mdm2, a RING ligase that acts on p53, and consequently activate the p53 pathway (10,11). However, only a few other inhibitors of RING ligases have been published (12,13), and none have been published that inhibit HECT ligases in vivo.…”
mentioning
confidence: 99%